Breakpoint Associated with a novel 2.3 Mb deletion in the VCFS region of 22q11 and the role of Alu (SINE) in recurring microdeletions - O'Reilly Richard L; Fan Yao-Shan; Siu Victoria; Zhang Yang; Uddin Raihan K; Rao Jay; Singh Shiva M (BMC, 2006)
Abstract Background Chromosome 22q11.2 region is highly susceptible to rearrangement, specifically deletions that give rise to a variety of genomic disorders including velocardiofacial or DiGeorge syndrome. Individuals with this 22q11 microdeletion syndrome are at a greatly increased risk to develop schizophrenia. Methods Genotype analysis was carried out on the DNA from a patient with the 22q11 microdeletion using genetic markers and custom primer sets to define the deletion. Bioinformatic analysis was performed for molecular characterization of the deletion breakpoint sequences in this patient. Results This 22q11 deletion patient was established to have a novel 2.3 Mb deletion with a proximal breakpoint located between genetic markers RH48663 and RH48348 and a distal breakpoint between markers D22S1138 and SHGC-145314. Molecular characterization of the sequences at the breakpoints revealed a 270 bp shared sequence of the breakpoint regions (SSBR) common to both ends that share >90% sequence similarity to each other and also to short interspersed nuclear elements/Alu elements. Conclusion This Alu sequence like SSBR is commonly in the proximity of all known deletion breakpoints of 22q11 region and also in the low copy repeat regions (LCRs). This sequence may represent a preferred sequence in the breakpoint regions or LCRs for intra-chromosomal homologous recombination mechanisms resulting in common 22q11 deletion.